Philosophy of Educational Policy: Problems, Challenges, and Possibilities - Rachmadani, Fadhila; Ahmad, Norainie (FOUNDASIA, 2025)
Educational policy is a conceptual basis that is essential for the implementation of education. Educational policy also holds an important position, role, and function in the implementation of education at the micro, meso, and macro scales. This article focuses on the problems, challenges, and future possibilities regarding educational policy from a philosophical perspective. This paper aims to explore the problems, challenges, and various future possibilities in the field of educational policy through the lens of philosophy, specifically ontology, epistemology, and axiology. This literature-based paper is a qualitative study that refers to John Ward Creswell 's book entitled "Qualitative Inquiry and Research Design: Choosing Among Five Approaches". This research is a type of library research using data collection techniques that involve reading literature sources such as books, journals, and studies, which are then classified for further analysis of the literature. The results of this study reveal the hidden philosophical meanings behind the problems and challenges of educational policy, serving as reflective material to consider and estimate various future possibilities concerning the development of educational policies deemed appropriate and suitable for formulation and implementation in the education sector. The findings of this study also pave the way for various studies in the field of educational policy analyzed through the 'lens' of philosophy.